Hall of Justice and Records - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
The Hall of Justice and the Hall of Records on the corner of Market and West St. James Street. On the far left of the image, down St. James Street, part of St. James Park can be seen. The building on the far left is the Hall Records, and next to it would be the county courthouse, obscured by the Hall of Justice in the center of the image. On the far right, looking down Market street the Electric Light Tower and City Hall are visible.